Death in the floating city - Alexander, Tasha (New York St. Martin's Minotaur, 2012)
Entreated for help by a childhood nemesis who has been wrongly accused of murder, Lady Emily launches an investigation in Venice that takes her from elegant palazzi to slums, libraries, and bordellos before she links the crime to a centuries-old puzzle.
115268
Keywords: Murder -- Investigation -- Italy -- Venice -- Fiction; Aristocracy (Social class) -- Fiction; Literary Criticism -- American -- General; Murder -- Investigation; Criminal investigation -- Venice (Italy) -- Fiction; Italy -- Venice; Historical fiction; Detective and mystery fiction; Fiction; Mystery fiction